The Effect of Body Mass Index on Fundamental Motor Skills in Six-Year-Old Children of Isfahan City - Rokhsareh Badami; Maryam Nezakatalhosseini; Fahime Rajabi; Mansoore Jafari (University of Tehran, 2014)
The present study was designed to determine the effect of different levels of body mass index (BMI) on fundamental motor skills in 6-year-old children of Isfahan city. For this purpose, fundamental motor skills of 19 underweight children (grade 3 thinness) and 19 children with normal weight and 19 overweight children who were matched according to their gender and socioeconomic background were assessed using the Movement Assessment Battery for Children (M-ABC). Among 8 items of M-ABC, normal weight and overweight children differed on only one-leg balance with preferred leg and normal weight and underweight children differed on only walking heels raised item. However, the total motor impairment score which was calculated by the summation of the 8 item scores was higher in underweight and overweight children than their normal weight peers.